Improvement of active power factor correction circuit for switch mode power supply using fly back and boost topology - Mahmud, Md. Walid; Alam, AHM Zahirul; Rahman, Dewan Atiqur (IEEE, 2018)
At present there is expanding requests of high power component and low total harmonic distortion (THD) in the current drawn from the source. Additionally there is a necessity of good power quality. Striking endeavors have been made for the improvement of the PFC converters. This paper aims to improve the power factor near to unity by using Fly Back Topology and Boost topology. Fly Back topology is called an isolated topology due to the use of transformer. It begins with simple circuits with a gradual increase in complexity by inclusion of new components and their subsequent effects on the current and voltage waveforms. The advantages of this method are fast response time, absence of switching problem and correction of power factor efficiently.